PENENTUAN KELAYAKAN ALIH FUNGSI LAHAN BEKAS TAMBANG BATUBARA LAPANGAN X TANJUNG ENIM BERDASARKAN CITRA SENTINEL-2 - Valentin, Ferdio; Sitompul, Ivana Jayarani; Fahlefi, M. Reza; Dani, Ilham (Universitas Muhammadiyah Gorontalo, 2024)
Coal exploitation in Tanjung Enim, Muara Enim Regency, South Sumatra Province is still being conducted. Some of the 7621 hectares of land that is a coal mining production area is no longer used and leaves ex-mining land. Ex-mining land that is left open will affect the ecosystem and harm the surrounding community, so it is necessary to change the function of ex-mining land. The purpose of this research is determining the feasibility of changing the function of the former mining area. The data used is data from the Sentinel-2 satellite by utilizing band 4, band 8, and band 11 to produce a vegetation index from the Normalized Difference Vegetation Index (NDVI) and a fire index from the Normalized Burn Ratio (NBR) in 2019, 2021, and 2023. The threshold value used to declare the research area suitable for land use changes is -0.2 for n and 0.1 for m. From the data processing, it is found that the NDVI 2019 is 0.3 and -0.1 for NBR 2019, 0.24 for NDVI 2021 and -0.104 for NBR 2021, and 0.19 for NDVI 2023 and -0.108 for NBR 2023. Values of NDVI that are greater than the threshold (n) and values of NBR that are smaller than the threshold (m) indicate the feasibility of the land use change. This leads to the conclusion that the research area is suitable for conversion of land use.